Pain neuroscience education in patients with chronic musculoskeletal pain: an umbrella review - Cuenca-Martínez, Ferran; Suso-Martí, Luis; Calatayud, Joaquín; Ferrer-Sargues, Francisco José; Muñoz-Alarcos, Vicente; Alba-Quesada, Patricio; Biviá-Roig, Gemma (Frontiers in Neuroscience, 2023)
In recent years, pain neuroscience education (PNE) has been the focus of extensive research in the scientific literature in the field of physical therapy, but the results obtained are controversial and its clinical application remains unclear. The main aim of this umbrella review was to assess the effectiveness of PNE in patients with chronic musculoskeletal pain (CMP). We searched systematically in PubMed (Medline), PEDro, EMBASE, CINAHL and PsycINFO. Methodological quality was analyzed using AMSTAR-2 scale. 16 systematic reviews were included. A qualitative synthesis was performed for the following sets of patients with CMP: overall CMP, chronic spinal pain, patients with fibromyalgia and patients with osteoarthritis. In general terms, it seems that the addition of the PNE-based intervention to other treatments, mostly exercise-based interventions although we might refer to it in terms of a multimodal approach, leads to greater clinical improvements than the multimodal approach alone. We have found this especially in the reduction of the influence of psychosocial variables. However, it seems that studies testing the effectiveness of PNE in isolation, systematic reviews with or without meta-analysis did not show statistically significant improvements overall in terms of pain intensity, disability levels or psychosocial variables. There is a great heterogeneity in the results obtained and the PNE protocols used, a critically low quality in the reviews included and a very high overlap, so there is a need to improve the studies in this field before clinical application.